Short Note: Sedimentology of Bali Touristic Locations - Tanah Lot and Uluwatu - Darman, Herman (Berita Sedimentologi, 2012)
Tanah Lot and Uluwatu are famous touristic sites in the southern part of Bali, and part of the Sunda Volcanic Arc. Most visitors come to these places to enjoy the scenery and visit the temple. The uniquity of these sites, however, is the result of the specific local geological setting in which they are located.The Tanah Lot temple was built on top of Quarternary volcanic clastic deposits, and was separated from the main island because of erosional processes. Uluwatu which is well known for the temple was built on a Miocene limestone cliff. Due to the excellent exposure of the geology, both localities allow for studying the sedimentary history which has resulted in these remarkable sites.This article discusses the stratigraphy and sedimentological features seen on these two locations. Despite the excellent exposure, both locations have received very little attention and only few studies have been reported. Both sites but especially the Uluwatu cliff, provides an excellent lateral exposure, allowing to discuss the depositional in a spatial framework. The outcrops in both locations show close relationship between volcanic activity and carbonate deposition.